2020
DOI: 10.1002/jcp.29501
|View full text |Cite
|
Sign up to set email alerts
|

miR‐129‐5p inhibits proliferation, migration, and invasion in rectal adenocarcinoma cells through targeting E2F7

Abstract: microRNAs (miRNAs), a kind of small noncoding RNAs, are considered able to regulate expression of genes and mediate RNA silencing. miR‐129‐5p was shown to be a cancer‐related miRNA. However, the influence of miR‐129‐5p in rectal adenocarcinoma (READ) development remains to be determined. Based on the TCGA data, downregulation of miR‐129‐5p in READ samples was observed. Manual restoration of the miR‐129‐5p in SW1463 and SW480 cell lines significantly inhibited invasion, migration, and proliferation of READ cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…Recent studies have confirmed our conclusion: E2F7 has been proven to overexpressed in LUAD, and its expression is regulated by SNHG6 through the competitive sponging of miR-26a-5p, which promotes tumor growth and metastasis (25,26). E2F7 plays an indispensable role in a variety of tumors, such as gallbladder cancer (27), rectal adenocarcinoma (28), and breast cancer (29), indicating that E2F7 may be a potential prognostic marker. The high expression of E2F7 is related to short patient survival time and can promote NSCLC cell proliferation, migration, and invasion (30).…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies have confirmed our conclusion: E2F7 has been proven to overexpressed in LUAD, and its expression is regulated by SNHG6 through the competitive sponging of miR-26a-5p, which promotes tumor growth and metastasis (25,26). E2F7 plays an indispensable role in a variety of tumors, such as gallbladder cancer (27), rectal adenocarcinoma (28), and breast cancer (29), indicating that E2F7 may be a potential prognostic marker. The high expression of E2F7 is related to short patient survival time and can promote NSCLC cell proliferation, migration, and invasion (30).…”
Section: Discussionsupporting
confidence: 77%
“…7 Accumulating evidence proves that miRs take part in the progression of CRC, such as miR-143 and miR-145. 8 As a tumor suppressor, miR-129-5p participates in various tumors, like rectal adenocarcinoma 9 and gastric cancer. 10 It is reported that miR-129-5p expression is declined in CRC cell lines, and miR-129-5p can impede cancer cell proliferation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…E2F7 was identified as an miR-129-5p target that mediates miR-129-5p-induced effects. These results suggest that miR-129-5p could serve as an effective target for LARC that should be further studied [70].…”
Section: Mirnas As Potential Therapeutic Targets In Combination With mentioning
confidence: 83%